ANALISIS DAN USULAN PENINGKATAN EFEKTIVITAS MESIN CNC MILLING MENGGUNAKAN PENDEKATAN OVERALL EQUIPMENT EFFECTIVENESS (OEE): CNC Milling, OEE, Produktivitas, Fishbone Diagram, Efektivitas Mesin - Ganda Sirait; Arsyad Sumantika (LPPM Universitas Putera Batam, 2026)
Increasing competition in the manufacturing industry requires companies to improve productivity and machine utilization effectiveness. CNC Milling machines play a crucial role in manufacturing processes due to their ability to produce high-precision components. Therefore, machine performance and reliability significantly affect production efficiency. Common problems such as downtime, reduced operating speed, and product defects can decrease machine effectiveness. This study aims to analyze the effectiveness level of CNC Milling machines using the Overall Equipment Effectiveness (OEE) method and identify factors causing low effectiveness through Fishbone Diagram analysis. Data were collected from production and maintenance records during January–March 2025. OEE calculations were conducted based on three main indicators: Availability Rate, Performance Rate, and Quality Rate. The results show that the average Availability Rate reached 88.76%, Performance Rate 83.24%, and Quality Rate 97.45%, resulting in an OEE value of 71.95%. This value is below the world-class standard of 85%. Fishbone Diagram analysis revealed that the major causes of low effectiveness originated from human, machine, method, material, and environmental factors. Improvement proposals include implementing preventive maintenance programs, enhancing operator competencies, improving operational procedures, and strengthening production monitoring systems.